On the role of dominance and nurturance in the confluence model: A person‐centered approach to the prediction of sexual aggression. Issue 3 (24th October 2016) - Troche, Stefan J.; Herzberg, Philipp Yorck
Abstract : Malamuth's (1998) confluence model holds that the combination of hostile masculinity, impersonal sexuality, and the constellation of high dominance and low nurturance plays a crucial role in explaining men's sexual aggression against women. Most studies on the confluence model concentrate on hostile masculinity and impersonal sexuality rather than dominance and nurturance. Using a person‐centered approach, we investigated whether sexual aggressive men could be better identified in a sample of 692 men when not only hostile masculinity and impersonal sexuality but also dominance and nurturance were used as indicators in a latent profile analysis. Regardless of whether dominance and nurturance were considered or not, latent profile analyses revealed a high‐risk group, which showed higher sexual aggression than other groups. In both cases, the sensitivity (i.e., the proportion of sexually aggressive men correctly assigned to the high‐risk group) was low (33% and 31%, respectively) but increased substantially for the identification of severe sexual aggression. The positive prediction value, however, increased from 68% to 78% when dominance and nurturance were considered as predictor variables in addition to hostile masculinity and impersonal sexuality, indicating that more men assigned to the high‐risk group were indeed sexually aggressive. These results demonstrate the power of the confluence model for identifying sexually aggressive men from a person‐centered perspective. They also point to the necessity of expanding this perspective by considering further (e.g., situational) risk factors, which have previously been identified as predicting sexually aggressive behavior in men. Aggr. Behav. 43:251–262, 2017. © 2016 Wiley Periodicals, Inc.